General estimates for the difference of operators. Issue 2 (21st March 2019) - Gupta, Vijay
Abstract : This paper deals with the quantitative estimates for the difference of operators having the same basis functions. The results essentially improve the earlier known results. In the end, some applications for the differences of Szász‐Mirakyan operators with its different variants are presented.